Increasing Student Activity and Motivation: Implementation of Cooperative Learning Models Type Teams Game Tournament - Salma Drayatun; Ayu Rahmawati (JURNAL PENA SAINS, 2017)
The main aim of this research is to apply a cooperative learning model that is cooperative learning model type TGT (Team Game Tournament) to increase student activity and motivation in biodiversity material, implemented in SMP Negeri 1 Kokop Bangkalan. As the subject of this class action research is the students of class VIID with 31 students. Based on the results of classroom action research that has been done, it can be concluded that science learning material of diversity of living creatures by using cooperative learning model TGT, learning activities and student motivation increased this can be seen from the test of student learning outcomes in the form of prestest and posttest. And the average value of questionnaire of motivation has given positive respons. It means motivation student increasing.